Influence of management on plankton community of fishponds during the dry and rainy seasons - Sipabua-Tavares, Lucia Helena; Millan, Rodrigo Ney; do Amaral, Atansio Alves (My University, 2010)
Aim: The present investigation aims at evaluating attention to the occurrence and abundance of planktonic communities in fishponds and their relationships to the management employed; Methods: Seven fishponds (V1-V7) fertilized with different treatments were analyzed by monthly sampling, taken between July and December/07, during both dry and rainy seasons; Results: Euglenophyceae and Chlorophyceae were most representative during the studied period. In the fishpond with organic fertilizer Cyanobacteria was more than 65 and 90% of total phytoplankton abundance in September and August, mainly represented by Microcystis sp. (14,595 and 22,500 ind.L-1, respectively). An inverse relationship occurred between Copepoda and Cladocera, and Copepoda and Rotifera were present in all fishponds during the both seasons. Diversity (H') and species richness was low and equitability indices generally showed the highest values for zooplankton. The lowest values were observed for phytoplankton during the rainy season; Conclusions: The use of organic fertilizer and the random emptying of the fishponds affected directly and species diversity and richness, with dominance of Cyanobacteria emphasizing the need to adopt a management technique to increase fishponds productivity and consequently, fish production.